Characteristics of laser-offset-TIG hybrid welding of AZ31Mg alloy with 6061Al alloy via Zn filler. (August 2022) - Lv, Xinze; Liu, Liming
Graphical abstract: Highlights: This work proposed a laser-offset-TIG hybrid welding method to join Mg-Al dissimilar metals, the joint strength is 1.3 times higher than that with normal laser-TIG hybrid welding. The laser-offset-TIG hybrid heat source can not only promote the wettability of filler metal, but also inhibit the formation of brittle Mg-Zn IMCs. The attraction effect of the laser to arc is conducive to reducing the heat input on Mg base metal. Abstract: This work proposed a laser-offset-TIG hybrid welding method to join AZ31 Mg alloy to 6061 Al alloy with Zn filler in lap configuration. Through the lateral offset of laser and arc, the wettability of filler metal was improved, and the amount of intermetallic compounds (IMCs) was well controlled. The spread width of filler metal increases from 2.13 mm to 3.49 mm and the reaction depth decreases from 0.91 mm to 0.66 mm as the offset distance increases from 0 mm to 2 mm. The major phases formed in joint are Al solid solution, MgZn2 IMCs, Zn solid solution and Mg32 (Al, Zn)49 ternary IMCs. At the appropriate offset distance of 2 mm, the coarse MgZn2 grains in fusion zone are refined to (Al)+(Zn)+MgZn2 eutectic, and the brittle Mg32 (Al, Zn)49 ternary IMCs in weld corner are eliminated. The maximum joint strength is 1190 N/cm, which is 1.3 times higher than that with normal laser-TIG hybrid welding.